2015
DOI: 10.1074/jbc.m114.618694
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA MiR-199a-5p Regulates Smooth Muscle Cell Proliferation and Morphology by Targeting WNT2 Signaling Pathway

Abstract: Background: MicroRNA miR-199a-5p, implicated in cell motility and proliferation, is highly expressed in bladder smooth muscle. Results: MiR-199a-5p regulates WNT, cytoskeleton, and cell cycle pathways in urothelial and smooth muscle cells and promotes myocardin-driven gene expression. Conclusion: MiR-199a-5p acts via its target WNT2 to control smooth muscle proliferation and morphology. Significance: MiR-199a-5p is a key modulator of smooth muscle hypertrophy, relevant for bladder organ remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…miR-199-5p is highly expressed in the bladder smooth muscle that has previously been found to regulate components of the intercellular junctions [269]. Recently miR-199a-5p was found to directly inhibit Wnt2 or Wnt-dependent cell proliferation and simultaneously activate myocardin and MRTF-A-dependent smooth muscle differentiation [270]. Attenuation of miR-199a-5p causes a significant reduction of the bladder smooth muscle cell size and increased cell proliferation.…”
Section: Microrna Regulation Of Wnt Signaling Pathways In the Contmentioning
confidence: 99%
“…miR-199-5p is highly expressed in the bladder smooth muscle that has previously been found to regulate components of the intercellular junctions [269]. Recently miR-199a-5p was found to directly inhibit Wnt2 or Wnt-dependent cell proliferation and simultaneously activate myocardin and MRTF-A-dependent smooth muscle differentiation [270]. Attenuation of miR-199a-5p causes a significant reduction of the bladder smooth muscle cell size and increased cell proliferation.…”
Section: Microrna Regulation Of Wnt Signaling Pathways In the Contmentioning
confidence: 99%
“…Normalized Ct values for 3-mRNA or 3-miRNA signatures of the samples with the known urodynamic status ( Figure 5, E and F) were employed in machine-based learning algorithms described in the Methods to train the model. Using the Ct values for either mRNA or miRNA signatures of the blinded samples as an input, the model allocated them to 3 groups corresponding to the predicted bladder functional state: BOO7, 24, 31, 32, 37, 38, 39, 40, 6, 5, 21, 22 and 23 belonged to the DO group; BOO16, 14, 15, 9, 8, 33, and 34 belonged to the BO group, and the remaining samples (BOO28, 29,30,41,42,10,11,12,13,17,18,19,20,4,3,2,1,25,26,27) were from the UA group. On the heatmaps, the samples were colored according to the machine-based group allocation (DO in blue, BO in green, and UA in orange) ( Figure 6, A and B).…”
Section: Ua (mentioning
confidence: 99%
“…Reliable markers of bladder function are urgently needed in order not to surpass the "point of no return," leading to bladder decompensation and failure. The studies of individual cellular signaling pathways conducted in animal models (5-7) identified some of the regulated genes typical for a specific symptomatic state; similarly, a number of regulatory miRNAs have been implicated in bladder pathologies (8)(9)(10)(11)(12) and function (13). Increasing evidence indicates that miRNAs may play a role in the regulation of urothelial permeability (14) and bladder contractility (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al 2012, Taipaleenmaki et al 2012, Wei et al 2012, Xu et al 2012a,b, Chiyomaru et al 2013. Furthermore, these miRNAs could mediate WNT signaling (Chiyomaru et al 2013, Nagano et al 2013, Guo et al 2014, Rathod et al 2014, Hashemi et al 2015, a crucial factor in decreased bone formation in response to GCs. Therefore, we first examined whether these six miRNAs were involved in the regulation of osteoblast proliferation by GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results of previous studies have indicated that many of these miRNAs, including miR-27a, miR-29a, miR-34a, miR-125b, miR-199a, and miR-574, could mediate cell proliferation , Ma et al 2012, Wei et al 2012, Xu et al 2012a,b, Chiyomaru et al 2013. Moreover, these six miRNAs have been reported to regulate the WNT signaling pathway (Chiyomaru et al 2013, Nagano et al 2013, Guo et al 2014, Rathod et al 2014, Hashemi et al 2015, which is a crucial regulator of GC-mediated bone acquisition and remodeling activities. Thus, we proposed the hypothesis that these molecules might be involved in GC-repressed osteoblast proliferation.…”
Section: Introductionmentioning
confidence: 99%